Analysis Of The Application Of The Accounting Cycle In The Kalamansi Orange Business, MSMEs Sahabat Kita In The Village Of Pondok Kubang - Ayu Lestari, Desmita (Journal of Management, Economic, and Accounting, 2022)
The purpose of this study was to determine the extent to which the application of accounting carried out by UMKM Sahabat Kita in Pondok Kubang Village in implementing the accounting cycle, the study was conducted using a qualitative approach. The place of this research is one of the Kalamansi Orange business UMKM. Data collection is done by observation, interviews and dokumentation. The researcher conducts a survey then observes, searches and cellects data. The resoult of the study indicate that the Kalamansi Orange Business UMKM Sahabat Kita has not implemented an accounting cycle that is in accordance with the accounting cycle according to Pura, there are only a few items that are appropriate, such as the General Ledger, Profit and Loss Statement, Statement of Changes in Equity, Statement of Financial Position and Inverting Journal.